Production of Poly(3-Hydroxybutyrate-Co-3-Hydroxyvalerate) by Marine Archaea Haloferax mediterranei Dsm 1411 with Yeast Extract As Nutrient Source - Susiana Melanie; James Winterburn (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2017)
In many countries, most of household goods are made from polymer or plastic. The polymer manufacturing industry has been relying on fossil fuel-based raw materials which are non-biodegradable. Plastics derived from these non-biodegradable sources will be difficult to degrade in nature, which in turn will pollute the environment and harm the ecosystem. One way to reduce the ecosystem damages caused by petroleum-based plastic is by using biodegradable materials for plastic industry, such as Polyhydroxyalkanoates (PHA). Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) or PHBV is an example of PHA that can be produced by several types of microorganism, one of them is marine archaea Haloferax mediterranei. The objective of this study is to determine the productivity of marine archaea H. mediterranei cultures to produce PHBV with yeast extract as main nutrient sources. Experiments and analysis were conducted in triplicate and batch operating system. During the fermentation process, optical density, glucose levels, phosphorus levels, pH, and dry cell weight (DCW) were observed. The final product was then analysed using GC-MS to determine 3HB (3-hydroxybutyrate) and 3HV (3-hydroxyvalerate) fraction composition in the PHBV. The results showed that the maximum specific growth rate (m) and doubling time (Td) of the H. mediterranei were 0.1258 hours-1 and 5.51 hours, respectively. H. mediterranei biomass increased until it reached stationary phase after 95 hours incubation. The PHBV content, dry biomass and yield of PHBV to substrate were 2.62 g/L, 29.1% and 0.27 g/g, respectively.